THE IMPLEMENTATION OF THE MIND MAPPING METHOD TO INCREASE STUDENTS’ WRITING SKILLS OF THE 12th GRADE OF SMA NEGERI 4 PEMATANGSIANTAR - Sidabutar, Yosefa Patresia; Pasaribu, Feronika Wasti; Sitorus, Rendy Yahya (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
Writing is the most difficult skill because we know that by writing it means we must be required to be able to compose language properly and correctly. To be able to write well, we must be able to think creatively and innovatively, to be able to produce a language that is worthy of writing. In this study, researchers found that students of SMA Negeri 4 Pematangsiantar, especially grade 12 science, had problems writing an incident or explaining something by writing a description of the incident. This happened because they did not have detailed ideas when they were asked to explain the picture or the incident. The research was to find out whether there was effectiveness in the mind mapping method, especially for grade 12 students at SMA Negeri 4 Pematangsiantar, and also the researchers wanted to see if students were able to improve their writing using the mind mapping method. Based on the data generated from students’ research in improving their writing skills through the mind mapping method, it can be concluded that the average of the pre-test and post-test obtained in the first cycle is 32.31 and 58.28 and a significant difference is found in the second cycle, which is 49.90 and 71.09. And it can be seen that the value after using the mind mapping method increased in cycle 2.